Synchronization of Electronic Medical Record Implementation Guidelines in National E-Health Strategies - Rezky Ami Cahyaharnita (Universitas Katolik Soegijapranata Semarang, 2019)
Medical records are made in writing, complete and clear or electronically. Medical records are the basis of medical services to patients. Paper medical records increase the amount of paper waste in Indonesia. A national e-health strategy is a comprehensive approach to efforts in the national health sector. Electronic medical records are more effective because of better time management. The formulation of the problem in this article covers the reasons, criteria, and implementation of electronic medical records. The research method used is descriptive qualitative research with a statute approach. The criteria for a good electronic medical record are integrated data from various sources, data collected at the service point, and supporting service providers in decision making. The expected electronic medical record is to be integrated with the health service facility information system program without neglecting the confidentiality aspect. Therefore, the government needs to make regulations on the technical implementation of electronic medical records.